Unexpected spatial population ecology of a widespread terrestrial salamander near its southern range edge. Issue 6 (12th June 2019) - Hernández-Pacheco, Raisa; Sutherland, Chris; Thompson, Lily M.; Grayson, Kristine L.
Abstract : Under the current amphibian biodiversity crisis, common species provide an opportunity to measure population dynamics across a wide range of environmental conditions while examining the processes that determine abundance and structure geographical ranges. Studying species at their range limits also provides a window for understanding the dynamics expected in future environments under increasing climate change and human modification. We quantified patterns of seasonal activity, density and space use in the eastern red-backed salamander ( Plethodon cinereus ) near its southern range edge and compare the spatial ecology of this population to previous findings from the core of their range. This southern population shows the expected phenology of surface activity based on temperature limitations in warmer climates, yet maintains unexpectedly high densities and large home ranges during the active season. Our study suggests that ecological factors known to strongly affect amphibian populations (e.g. warm temperature and forest fragmentation) do not necessarily constrain this southern population. Our study highlights the utility of studying a common amphibian as a model system for investigating population processes in environments under strong selective pressure.